Kompleksnyi kontrol' v sisteme podgotovki junych kon'kobezhtsev - Bakhrakh, I. I.; Doktorevic, A. M. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
There are presented the basics of a useful system of komplex control in speed skating for young athletes. For instance it is shown a modell of the optimal parameters of the strength impulse for the pases and stride (kg/s) in young speed skarters (8-16 years old) on ice. Further on there are presented a modell of kinematic parameters during the gliding strike and morpho-functional parameters for perspective young skaters in the age of 8-16.